Peran Biro Kesra Sekretariat Daerah Provinsi Jawa Timur dalam Pemberian Bantuan Sosial Jaminan Hidup Tahap Akhir Bagi Eks. Korban Konflik Sosial Sampang Tahun 2023 - Mumtazah, Shofy Salsabil; Wahyudi, Kalvin Edo (IAI Nasional Laa Roiba Bogor, 2024)
The social conflict between the Syiah and Sunni groups in Sampang Regency, East Java due to differences in understanding has caused social risks for the Shia Group in the form of discrimination which led to rejection, requiring them to leave their homes and take refuge in the Jemundo Flat in Sidoarjo Regency. As stated in the East Java Governor Regulation No. 44 of 2021 which also discusses social assistance, the East Java Provincial Welfare Bureau participated in handling social risks due to the conflict that occurred by providing social assistance in the form of life insurance in cash for the victims. However, there are discrepancies in its implementation, namely related to the period of providing social assistance that exceeds the grace period for conflict. This study aims to determine the role of the Kesra Bureau in providing social assistance in the form of a final stage of life insurance at the end of October 2023 for Ex-Sampang Social Conflict Victims in 2023. This research is descriptive qualitative using the Miles and Huberman analysis method. Primary data used was obtained through observation, documentation and interviews as well as secondary data through related journals and websites. The research locus is located at the Bureau of Welfare of the Regional Secretariat of East Java Province. The results showed that the Welfare Bureau had carried out the provision of social assistance in the form of life insurance in the final stage on October 30, 2023 at the Jemundo Flat, Sidoarjo Regency. This indicates that the Welfare Bureau with the help of relevant stakeholders has carried out its role in providing late-stage social assistance according to the criteria for providing social assistance as in Governor Regulation No. 44 of 2021 Article 30, namely meeting the requirements of beneficiaries, selective, temporary and not continuous, except in certain circumstances it can be sustainable, and adjusted to the intended use.